Treatment tolerability and toxicity of postoperative proton beam therapy for gynecologic malignancies: results of the prospective phase 2 APROVE trial - Arians, Nathalie; Lindel, Katja; Krisam, Johannes; Oelmann-Avendano, Jan Tobias; Meixner, Eva; König, Laila; Hörner-Rieber, Juliane; Wark, Antje; Forster, Tobias; Weykamp, Fabian; Uzun-Lang, Kristin; Schneeweiss, Andreas; et al. (International journal of radiation oncology, biology, physics, 2023)
Purpose - The APROVE study is a prospective one-arm phase-2 study investigating the safety and treatment tolerability of postoperative proton beam therapy in women with uterine cervical or endometrial cancer. In this analysis, we report the primary study endpoint of safety and treatment tolerability as well as toxicity rates and progression-free survival (PFS). - Methods and Materials - 25 patients were treated with postoperative proton beam therapy with a total dose of 45 to 50.4 Gy (RBE) in 5 to 6 × 1.8 Gy (RBE) fractions weekly using active raster-scanning intensity modulated proton beam therapy (IMPT). Sequential or simultaneous platinum-based chemotherapy was administered if indicated. The primary endpoint was defined as the lack of any acute ≥grade 3 gastrointestinal (GI) or urogenital (GU) toxicity according to the Common Terminology Criteria for Adverse Events v 4.0 or premature treatment abortion. Secondary endpoints were clinical symptoms and toxicity, quality of life, and PFS. - Results - All patients completed IMPT according to the protocol, with a median treatment duration of 43 days (range, 33 to 51 days). No patient developed gastrointestinal or genitourinary toxicity ≥grade 3, and the treatment tolerability rate was 100%. Therefore, the null hypothesis H0: Tolerability Rate ≤80% could be rejected in favor of the alternative hypothesis H1: Tolerability rate >80% using an exact binomial test with a one-sided significance level of α = 10% (one-sided P value P = .0059). The median follow-up time after the end of IMPT was 25.1 months (range, 20.2 to 50.3 months). 18 of 25 (75%) patients completed the study follow-up of 24 months. 7 patients had progressive disease. Kaplan-Meier-estimated mean PFS was 39.9 months (95% confidence interval: 33.37 to 46.5 months). - Conclusions - Postoperative IMPT is a safe treatment option for cervical and endometrial cancer patients, with only low-grade acute and late toxicities. Larger randomized trials are necessary to further assess the potential of IMPT and improve patient selection.
Online verfügbar: 13. Januar 2023, Artikelversion: 22. Juni 2023
Gesehen am 06.12.2023